Odpowiedź :
Rozwiązanie równania :
[tex]\frac{6x-1}{3x-2}=3(x+\frac{2}{3})\\\\3x-2\neq0\rightarrow x\neq\frac{2}{3}\\\\\frac{6x-1}{3x-2}=3x+2\\\\(3x+2)(3x-2)=6x-1\\\\9x^2-4-6x+1=0\\\\9x^2-6x-3=0\\\\a=9, \ b=-6, \ c=-3\\\\\Delta=b^2-4ac\rightarrow(-6)^2-4\cdot9\cdot(-3)=36+108=144\\\\\sqrt{\Delta}=\sqrt{144}=12\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\rightarrow\frac{-(-6)-12}{2\cdot9}=\frac{-6}{18}=-\frac{1}{3}\in\mathbb{D}\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\rightarrow\frac{-(-6)+12}{2\cdot9}=\frac{18}{18}=1\in\mathbb{D}[/tex]